Functionally diverse reef-fish communities ameliorate coral disease - Raymundo, L.; Halford, Andy; Maypa, A.; Kerr, A. (National Academy of Sciences, 2009)
Coral reefs, the most diverse of marine ecosystems, currently experience unprecedented levels of degradation. Diseases are now recognized as a major cause of mortality in reef-forming corals and are complicit in phase shifts of reef ecosystems to algal-dominated states worldwide. Even so, factors contributing to disease occurrence, spread, and impact remain poorly understood. Ecosystem resilience has been linked to the conservation of functional diversity, whereas overfishing reduces functional diversity through cascading, top-down effects. Hence, we tested the hypothesis that reefs with trophically diverse reef fish communities have less coral disease than overfished reefs. We surveyed reefs across the central Philippines, including well-managed marine protected areas (MPAs), and found that disease prevalence was significantly negatively correlated with fish taxonomic diversity. Further, MPAs had significantly higher fish diversity and less disease than unprotected areas. We subsequently investigated potential links between coral disease and the trophic components of fish diversity, finding that only the density of coral-feeding chaetodontid butterflyfishes, seldom targeted by fishers, was positively associated with disease prevalence. These previously uncharacterized results are supported by a second large-scale dataset from the Great Barrier Reef. We hypothesize that members of the charismatic reef-fish family Chaetodontidae are major vectors of coral disease by virtue of their trophic specialization on hard corals and their ecological release in overfished areas, particularly outside MPAs.